(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Improving the quality of work of paramedical staff is reaching a new level with the help of modern technologies. Modern information and communication technologies, artificial intelligence systems, digital health capabilities and advanced diagnostic methods play an important role in increasing efficiency in medical practice. These innovations serve not only to improve the quality of service provided to patients, but also to significantly increase the productivity of medical staff.